THE IMPACT OF OCCUPATIONAL HEALTH, SAFETY (K3) PROGRAM AND WORK ENVIRONMENT ON EMPLOYEE COMMITMENT OF PT PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Delyana Rahmawany Pulungan (CERED Indonesia Institute, 2020)
This study aims to determine the influence of occupational safety health program (K3) and work environment on employee commitment to PT Perkebunan Nusantara III (Persero). The population in this study is all employees at PT Perkebunan Nusantara III (Persero) numbered 925 people. Determining the number of samples taken as respondents using slovin formula, the sample in this study was 87 employees of PT Perkebunan Nusantara III (Persero). The data collection techniques in this study are quesioner list, interview and documentation studies. While the data analysis techniques used are classic assumption test, multiple regression, t test, and F test and determinant coefficient. The K3 program significantly affects the employee commitment of PT Perkebunan Nusantara III (Persero) Medan, which is indicated by a significant yield of 4,962 (sig 0,000) whereas significantly t is smaller than a. = 0.05). The work environment significantly affects the employee commitment of PT Perkebunan Nusantara III (Persero) Medan, which is indicated by a significant yield of 2,335 (sig 0.022), whereas significantly t is smaller than a. = 0.05. The K3 program and work environment significantly impacted the employee commitment of PT Perkebunan Nusantara III (Persero) Medan, which was demonstrated by a significant result of 21,915 with a sig of 0.000<a..